Bahasa Persuasif Sales Promotion Girls dalam Pemasaran Produk kepada Konsumen - Nur, Muhammad Fajrin; Usman, Usman; Sultan, Sultan (Nuances of Indonesian Language, 2023)
This study aims to: describe the persuasive language forms of sales promotion girls in product marketing; describe the function of persuasive language in captivating customers. This type of research is qualitative research. The data of this research are phrases, clauses, and sentences that contain persuasive elements when offering products to consumers. The source of the data in this study is the persuasive language of sales promotion gils in product marketing to consumers. Data analysis was carried out through the stages of data reduction, data presentation, and conclusions. The results of the study revealed that the persuasive form used by SPG when offering products was in the form of affirmations, forms of rewards, forms of offering several products, and forms of praise. The function of persuasive language used by SPG is the function of providing information, the function of product introduction, the function of added value. The use of several forms of persuasion is caused by consumers who come from different backgrounds.